UKRAINE WITHIN THE WORLD TRENDS OF THE HIGH-TECH PRODUCTS EXPORT MARKET - Belov, Alexander (Social Economics, 2022)
Abstract. The article is devoted to the research of world tendencies of the market of export of high - tech products and definition of features of dynamics and place in it of Ukraine. This study notes that the ability to generate and implement its own innovations and produce and improve high-tech goods and services will ensure strong competitiveness of the country, its financial stability and determine its place in the global economic environment of the future. The study based on the author’s methodology "analysis of speed and acceleration", which involves the calculation and economic feasibility of these indicators and allows you to assess the country’s potential to change trends. I analyzed the structure of exports of high-tech products in the world by countries and the dynamics of its volume by leading countries and Ukraine. I built rankings of countries on the absolute value of the rate of change in high-tech exports. I was studied the dynamics of speed and acceleration of changes in the volume of exports of high-tech products by country and grouped according to the ratio between these indicators. I determined that one of the important reasons for Ukraine’s insignificant place in the world market of high-tech products is the state policy in the field of science, technology and industry, which has been implemented in the country for the past 30 years; reducing the role of science in the economy by transferring it from the determining factor of production ("vector of development") to the "vector of pride". I showed that Ukraine’s stay in the 2nd group in 2019-2020 indicates the potential to change the situation, as the impact of factors affecting high-tech exports is positive, but still insufficient for the country’s transition to accelerated growth. I believe that providing conditions at the state level for investment in high-tech industries of the country will contribute to this growth.